Leaf silica concentration in Serengeti grasses increases with watering but not clipping: insights from a common garden study and literature review - Quigley, Kathleen M.; Anderson, T. M. (Frontiers in Plant Science, 2014)
Grasses (Poaceae) lack the complex biochemical pathways and structural defenses employed by other plant families; instead they deposit microscopic silica (SiO2) granules in their leaf blades (i.e. phytoliths) as a putative defense strategy. Silica accumulation in grasses has generally been considered an inducible defense; other research suggests silica accumulation occurs by passive diffusion and should therefore be closely coupled with whole plant transpiration. We tested the hypothesis that grasses increase leaf silica concentration in response to artificial defoliation in a common garden study in the Serengeti ecosystem of East Africa. Additionally, a watering treatment tested the alternative hypothesis that leaf silica was largely driven by plant water status. Leaf silica content of two dominant C4 Serengeti grass species, Themeda triandra and Digitaria macroblephara, was quantified after a 10-month clipping x water experiment in which defoliation occurred approximately every two months and supplementary water was added every two weeks. Themeda had greater silica content than Digitaria, and Themeda also varied in foliar silica content according to collection site. Clipping had no significant effect on leaf silica in either species and watering significantly increased silica content of the dominant tall grass species, Themeda, but not the lawn species, Digitaria. Our data, and those collected as part of a supplementary literature review, suggest that silicon induction responses are contingent upon a combination of plant identity (i.e., species, genotype, life history limitations) and environmental factors (i.e., precipitation, soil nutrients, grazing intensity). Specifically, we propose that an interaction between plant functional type and water balance plays an especially important role in determining silica uptake and accumulation.